Use of Different Murder Weapons by a Single Murderer: Two Case Reports - Eradil Orazhkan; Tao Pu; Longlong Wang; Zhimin Wang; Zhiwei Zhu; Rufeng Bai (Wolters Kluwer Medknow Publications, 2016)
Homicide is an extremely serious crime, and although the offender usually uses the same weapon to initially injure and complete the killing, there are exceptions. We report two cases in which a single murderer killed a victim using different weapons and summarize several situations in which a murderer might use different weapons to kill. The number of murders should be determined and estimated after a comprehensive complicated investigation of the scene, careful examination of the victim's injuries, and evaluation of evidence reported by eyewitnesses.